Compliance of Government and Business Knowledge Generating Modes in CEE Countries - Davor Vlajcic (Communications of International Proceedings, 2021)
The growth prospects of individual post-socialist economies are largely believed to depend upon the successful transformation of their inherited technological capacities. The transformation of pre-transition, government dominated R D models towards market-driven (“business dominated”) R&D models raises questions regarding their compatibility, which poses a threat to government and business R&D integration. Furthermore, new market contexts and in the wake of uncertainties regarding the allocation of technological resources, transformation success is additionally complicated. This research addresses the problem of government and business R&D sector compatibility, observing R&D resource allocation strategies. Compliance of resource allocation strategies will provide us with evidence of the successes of R&D sector transition processes. Estimation procedures were conducted using a panel vector autoregression approach that controlled for endogeneity and enabled the determination of links between variables. The results indicate that, despite the rapid and significant innovation system transformations made during the transition period, compliance between the government’s and businesses’ preferred modes of knowledge generation was achieved.
Keywords: CEE; Inherited technological capacities; Research & Development; Government economy; Market economy; Technology portfolio.